Acute and subacute toxicities of the saponin mixture isolated from Schefflera leucantha Viguier - Witthawaskul P. (2014)
Acute toxicity of the bronchodilator saponin mixture isolated from Schefflera leucantha Viguier leaves was investigated in comparison with the methanol and the water extract of this plant. Oral doses of 5000mg/kg of the methanol extract, the water extract and the saponin mixture did not produce mortality or significant changes in the general behavior and gross appearance of internal organs of rats. Subacute toxicity of the saponin mixture was evaluated with the dose of 1000mg/kg, orally for 14 days. An extra group (satellite group) was given saponin mixture and kept for a further 14 days after treatment. All animals did not show signs of toxicity during the experimental period. Liver weights of the saponin-treated and the satellite male groups were higher whereas testis weight were lower than those of the control group which received distilled water. However, the histological examination of various organs revealed that there were no differences between the control and the treated rats. BUN, Cr, AST, ALT and ALP levels increased in saponin-receiving rats. It is possible that the saponin mixture directly impacts on the liver and the kidney functions. © 2003 Elsevier Ireland Ltd. All rights reserved.